Analyzing the CP nature of a new scalar particle via S → Zh decay - Bauer, Martin; Neubert, Matthias; Thamm, Andrea (Arxiv, 2016)
Scalar particles $S$ which are singlets under the Standard Model gauge group are generic features of many models of fundamental physics, in particular as possible mediators to a hidden sector. We show that the decay $S→ Zh$ provides a powerful probe of the CP nature of the scalar, because it is allowed only if $S$ has CP-odd interactions. We perform a model-independent analysis of this decay using an effective Lagrangian and compute the relevant Wilson coefficients arising from integrating out heavy fermions to one-loop order.